Penyuluhan Pencegahan Stunting Sejak Dini pada Remaja bagi Siswa Sekolah Menengah Atas di SMAN 4 Palopo - Wulandari, Alda; Zamli; Ahmad.R.Mutaqqien Almaidin (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
Stunting is a chronic nutritional problem that has long-term impacts on the physical and cognitive growth and productivity of future generations. Adolescent girls play a crucial role in preventing stunting because they are the future mothers who will determine the nutritional status of their children. This community service activity aims to increase adolescent girls' understanding of the importance of early stunting prevention. The activity was held on July 17, 2025, at SMAN 4 Palopo. The activity included lectures, interactive discussions, and the distribution of leaflets to 80 second- and third-grade students. The results showed an increase in participants' understanding of the definition, causes, impacts, and role of adolescents in stunting prevention. Participants were highly enthusiastic, and the discussion was lively. This activity demonstrates that educational approaches in schools are effective in increasing adolescents' knowledge about nutritional health issues. It is hoped that similar activities can be held regularly and sustainably.